Single domain antibodies from camelids in the treatment of microbial infections - De Greve, Henri; Fioravanti, Antonella (Frontiers in Immunology, 2024)
Infectious diseases continue to pose significant global health challenges. In addition to the enduring burdens of ailments like malaria and HIV, the emergence of nosocomial outbreaks driven by antibiotic-resistant pathogens underscores the ongoing threats. Furthermore, recent infectious disease crises, exemplified by the Ebola and SARS-CoV-2 outbreaks, have intensified the pursuit of more effective and efficient diagnostic and therapeutic solutions. Among the promising options, antibodies have garnered significant attention due to their favourable structural characteristics and versatile applications. Notably, nanobodies (Nbs), the smallest functional single-domain antibodies of heavy-chain only antibodies produced by camelids, exhibit remarkable capabilities in stable antigen binding. They offer unique advantages such as ease of expression and modification and enhanced stability, as well as improved hydrophilicity compared to conventional antibody fragments (antigen-binding fragments (Fab) or single-chain variable fragments (scFv)) that can aggregate due to their low solubility. Nanobodies directly target antigen epitopes or can be engineered into multivalent Nbs and Nb-fusion proteins, expanding their therapeutic potential. This review is dedicated to charting the progress in Nb research, particularly those derived from camelids, and highlighting their diverse applications in treating infectious diseases, spanning both human and animal contexts.